Characteristic of CD4+CD25+ T Cells in Chronic Myeloid Leukemia Patients Treated with Imatinib Mesylate with Different BCR-ABL Transcripts Levels Response (Medico Legal Update, 2021)
Background: Several clinical trials on cancer showed a correlation between elevated levels of regulatoryT cells with either poor prognosis or poor response to some therapies. Hence, in this study we tried tomeasure the regulatory T cells (CD4+CD245+) count and to evaluate the program death receptor 1(PD1)as a one of the main suppressive mechanisms that regulatory T cells use in CML patients with differentmolecular response to imatinib therapy. Method: Flow cytometry technique was used to analyze 30 sampleof optimal molecular response of CML patients (BCR-ABL transcripts ? 0.1%) and 30 sample of failuremolecular response patients (BCR-ABL transcripts >1%) with or without hematological failure, in order toassess the CD4+CD25+ T cells (Tregs) and PD1 expression on these cells. Thirty samples age and gendermatched were used as healthy controls. Results: A high proportion of CD4+CD25+ T cells was found infailure groups compared to control and optimal groups(P= 33.7 % washighly significant with high sensitivity and specificity. This value can be used to determine the failure fromthe optimal CML responders. There was no noticeable differences (P= 0.125) in PD1+ expression amongCD4+CD25+ T cells. Conclusion: A high percentage of Treg cells in the failure CML group might be anindication of immune escape of leukemic cells in those patients compared to the other investigated groups.